2000
DOI: 10.1182/blood.v96.5.1836.h8001836_1836_1843
|View full text |Cite
|
Sign up to set email alerts
|

Activation of macrophage cytostatic effector mechanisms during acute graft-versus-host disease: release of intracellular iron and nitric oxide–mediated cytostasis

Abstract: During acute graft-versus-host disease (GVHD) the activation of macrophages (Mφ) is mediated by 2 signals, interferon (IFN)-γ and bacteria-derived lipopolysaccharide (LPS). A cascade of inflammatory responses that includes the release of mediators of tissue injury follows Mφ activation. Among the tissues characteristically targeted during acute GVHD are epithelial tissues of the skin and gastrointestinal tract that normally undergo continuous proliferation and are therefore sensitive to cytostatic processes. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous studies have clearly demonstrated that NO has a marked effect on cellular Fe metabolism [25][26][27]32]. Indeed, NO-mediated Fe depletion of tumour target cells by activated macrophages could play an important role in immune surveillance [3][4][5]15,16,45]. Our previous studies have shown that NO-mediated Fe mobilization is potentiated by incubating cells with D-glucose due to the subsequent generation of GSH [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have clearly demonstrated that NO has a marked effect on cellular Fe metabolism [25][26][27]32]. Indeed, NO-mediated Fe depletion of tumour target cells by activated macrophages could play an important role in immune surveillance [3][4][5]15,16,45]. Our previous studies have shown that NO-mediated Fe mobilization is potentiated by incubating cells with D-glucose due to the subsequent generation of GSH [32].…”
Section: Discussionmentioning
confidence: 99%
“…130,131 As a result of activation during GVHD, macrophages produce NO and induce the release of iron from target cells, resulting in an inhibition of the recovery of injured target tissues by inhibiting proliferation of epithelial stem cells in the gut and skin. 132 More recently a central role of inflammatory cytokines in acute GVHD was confirmed in a murine study by using bone marrow chimeras wherein mortality and target organ injury was prevented by the neutralization of TNF-and IL-1 particularly for CD4-mediated acute GVHD but also in part, for CD8-mediated disease. 23 These inflammatory effectors may synergize with the lytic component provided by CTLs in a complex milieu of chemotactic signals and cytokine cascades resulting in the amplification of local tissue injury and further promotion of an inflammatory response, which ultimately leads to the observed target tissue destruction in the transplant recipient.…”
Section: Inflammatory Effectorsmentioning
confidence: 98%